Indonesia’s Digital Diplomacy: Problems and Challenges - Ludiro Madu (Universitas Muhammadiyah Yogyakarta, 2018)
This paper explains the recent development of Indonesia’s digital diplomacy—which Indonesia’s Ministry of Foreign Affairs (MOFA) has conducted—in responding to the growing challenges of information, communication, and technology (ICT) towards its national interest. The use of the internet and its social media has definitely changed the practices of diplomacy among sovereign states, including Indonesia. Analyzing the issue within the interplay between internet and diplomacy, this paper looks at the way Indonesia’s MOFA and its diplomats have kept up with the rapid development of the ICT by mastering the use of internet in winning people’s hearts and minds. Tracing back the MOFA’s policies and implementations of digital diplomacy through its website and other platforms of social media reveals its strong commitment in using digital diplomacy in managing its foreign relations in the recent internet era. Digital diplomacy has presented several benefits for having direct and interactive communication with foreign audiences. In addition, Indonesia’s digital diplomacy has also had to deal with various problems which are closely related to the increasing use of internet among states and non-state actors—both in domestic and international levels—which may put risk to state-to-state relations. Therefore, this paper argues that the response of Indonesia’s MOFA and its diplomats towards the increasing use of digital diplomacy would determine its capability in managing various problems and challenges of international relations in the recent internet era.